Metallic nanoparticles and nanostructures for bio-applications - Zhang, J.B.; Cheng, L.; Yung, L.Y.L.; Chua, S.S.; Sze, J.Y.; Zhu, S.L.; Ayi, T.C.; Jeevaneswaran, R. (2009)
This paper elaborates on approaches of synthesis of Au and Ag nanoparticles (NPs), deposition of colloid onto glass substrate and encapsulation of NPs with silicon dioxide (SiO(2)) thin shell. As one important bio application of metallic nanoparticles, both solution-based and substrate-based fluorescence enhancement tests are demonstrated.